2002
DOI: 10.1111/j.1559-1816.2002.tb01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy Assessment and Generalization in Physical Education Courses1

Abstract: Physical education courses can have effects that generalize past their immediate task as measured by increases in domain‐specific self‐efficacy. It was predicted that competitive combative courses like boxing would be more likely to have skills generalize to other domains than noncontact courses like swimming. A Physical Education Self‐Efficacy Scale was created that focused on 2 different domains of self‐efficacy: 1 specific to the course (physicality), and 1 in a disparate domain (leadership initiative). Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In contexts in which one has little chance for withdrawal, such as physical education programs requiring participation, expectancy beliefs are posited to predict performance and persistence, whereas task values are predictors of intentions for future participation (Dishman et al, 2004;Samuel & Gibb, 2004;Xiang et al, 2003;Xiang, McBride, & Guan, 2004). However, when one enters a context involving the freedom to withdraw, such as extracurricular sports, expectancy beliefs predict performance (Feltz & Mugno, 1983;McAuley, 1985) and effort/persistence (Cox & Whaley, 2004).…”
Section: Contextual Influencesmentioning
confidence: 96%
“…In contexts in which one has little chance for withdrawal, such as physical education programs requiring participation, expectancy beliefs are posited to predict performance and persistence, whereas task values are predictors of intentions for future participation (Dishman et al, 2004;Samuel & Gibb, 2004;Xiang et al, 2003;Xiang, McBride, & Guan, 2004). However, when one enters a context involving the freedom to withdraw, such as extracurricular sports, expectancy beliefs predict performance (Feltz & Mugno, 1983;McAuley, 1985) and effort/persistence (Cox & Whaley, 2004).…”
Section: Contextual Influencesmentioning
confidence: 96%
“…Self-efficacy beliefs also can generalize from one situation or task to another, depending on the similarities between the task demands and the skills and resources required to meet those demands (e.g., Samuels & Gibb, 2002;Weitlauf, Cervone, Smith, & Wright, 2001). In addition, research has shown that general self-efficacy beliefs can be enhanced through targeted interventions (e.g., Eden & Aviram, 1993).…”
Section: Self-efficacy and Personalitymentioning
confidence: 99%
“…Further, although parachute training is perhaps the most prevalent example of preparing individuals for the extreme strains of combat, it is not the only one. Others are for example boxing (Samuels & Gibb, 2002), combative training (Morales-Negron, 2009), survival training (Schmied et al, 2015), and scuba-diving (Colodro-Plaza, Garcés, López-García, & Colodro-Conde, 2015). They share similarities in that they present a perceived threat to life that requires active mastery and are all used in some part to prepare individuals for the stress of functioning under extreme contexts.…”
Section: Discussionmentioning
confidence: 99%